LUNG FUNCTION INDICES IN MALE WOODWORKERS AND HEALTHY WORKERS IN CENTRAL INDIA – A COMPARATIVE STUDY - PRAVIN SAINIKRAO GOWARDIPE; MOHAMMAD SHAHID USMAN; DURAIN FATIMA (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objectives: The objectives of the study were comparison of lung function indices in woodworkers and age, height, and weight-matched healthy workers other than woodworkers and comparison of lung function indices among woodworkers about the duration of exposure. Methods: A comparative study of spirometry was performed on 60 male woodworkers from the Lakadganj area of Nagpur city and 60 males of age, height, and weight-matched healthy workers other than woodworkers aged from 25 to 40 years. The study was performed in the laboratory of the Physiology Department, IGGMC Nagpur from January 2012 to September 2013. The Institute Ethics Committee approved the present study and it was completed in IGGMC Nagpur. Data collection from each individual was performed using a health history questionnaire, estimation of height (cm) with roll ruler wall mounted roll ruler wall mounted stature meter, weight (kg) with weight measuring device, and well-calibrated Spirometry device Physiopac Windows-based computerized Polygraph. Age, height, weight, body mass index, and lung function indices forced vital capacity (FVC), forced expiratory volume in 1st second (FEV1), forced expiratory flow25-75% (FEF25-75%), FEV1/FVC, and maximum voluntary ventilation (MVV) were included in the present study. Data analysis was performed using analysis of variance, unpaired t-test, and the Pearson correlation coefficient. Results: Comparison of FVC, FEV1, peak expiratory flow rate, FEF25-75%, FEV1/FVC (p<0.001), and MVV (p<0.05) shows statistical significance between woodworkers and healthy workers. A negative correlation was found between FVC and all groups (Group A [−0.28], Group B [−0.33], and Group C [−0.46]). A negative correlation was found for FEV1 in Group A (−0.08), and Group B (−0.20). A positive correlation was found for FEV1 in Group C (0.14). FEF25-75% showed a negative correlation in Group I (−0.03), and Group III (−0.19). Conclusion: FVC, FEV1, FEF25-75%, FEV1/FVC, and MVV decreased significantly in woodworkers as compared to age, height, and weight-matched healthy workers other than saw-mill workers. There was a significant decrease in FVC, FEV1, and FEF25-75% as the duration of exposure increased but had no significant effect on FEV1/FVC and MVV.